Work Motivation and Achievement of Health Officers in Basic Program Public Health Center in Sojol District - Sudirman Sudirman (Humanistic Network for Science and Technology (HNST), 2018)
The purpose of health development is essentially to realize a healthy Indonesia, which is an ability to reach quality health services, fair and equitable for all Indonesian. The low performance of health center in health service in Central Sulawesi is basically caused by several factors: lack of adequate health center, lack of motivation and dedication of staff. The present research aims to find out the relationship between work motivations of health worker toward achievement of target of its basic program. This was an observational analytic research to find out the relationship between variables quantitatively without giving intervention to variables be studied with cross sectional method. The location of the research was public health center in Sojol district. Sampling is carried out by using total sampling. Population of the research includes 40 health officers at Balukang and Tonggolobibi public health center. Based on the results with chi-square test, the value of p = 0.025 (p ≤ 0.05) indicates that there is a statistically significant correlation between work motivation of health worker and the achievement of basic program target of health center in Sojol. Keywords: Work motivation, Achievement, Basic program of health center